Shoreline survey data collected at Rialto and Kalaloch Beaches, Washington State, 2018-2019 - Miller, Ian (PANGAEA, 2019)
Data were collected using GNSS survey methods, with a differential GPS operating in Real Time Kinematic (RTK) mode. All data were collected with an AshTech ProMark 200 RTK-DGPS system connected to the Washington State Reference Network. Horizontal positions are referenced to NAD83(2011) and the vertical data are referenced to NAVD88(Geoid09). All survey data were collected with the GNSS system mounted on a 2.05 m rover pole, held level as a transect line was traced in a cross-shore orientation on the beach. The associated text files include the horizontal (HRMS) and vertical (VRMS) root-mean-square errors estimated by the GNSS system, as well as the RTK-DGPS status reported by the GNSS system at the time each point was collected. Times are referenced to local Pacific time (either PST or PDT). Most data in these files are intended to be used to calculate beach profiles, but two other data types were collected during each survey: 1) Grain size photos, the locations of which were surveyed in the field and denoted in the "Description" field. The photos are currently available by request. 2) The location of the most seaward presence of large wood on the profile. These data were collected as part of a one year project intended to characterize seasonal shoreline position variability on the complex shoreline of Washington's Olympic coast. The project was jointly supported by the North Pacific Coast Marine Resources Committee, Washington Sea Grant, and Peninsula College.
Keywords: Beach profiles; Olympic National Park; Washington Coast